Air Pollution as Correlates of Anxiety, Depression and Criminal Behaviour in Obio/Akpor Local Government Area in Rivers State - P. W., Iyagba (International Journal on Orange Technologies, 2022)
The study investigated air pollution as correlates of anxiety, depression and criminal behaviour (indoor and outdoor crimes) in Obio/Akpor Local Government Area in Rivers State. The study adopted correlation design. Population consisted of all the communities in Obio/Akpor LGA. A 3-year panel of 10 Obio/Akpor communities was collected and analyzed to investigate the effects of air pollution on anxiety, depression and three crime categories. Community-level air pollution data was sourced from the EPA between 2019 and 2021 on six major pollutants: carbon monoxide (CO), nitrogen dioxide (N02), sulfur dioxide (S02), total suspended particulate (TSP), particulate matter PMJO, and particulate matter PM 2.5. We standardized each of the six pollutants and then averaged the standardized scores to compute a composite measure of air pollution for each community. Community-level crime data from the Crime Fighters Program was collected from the Nigeria Police Force. A self-structured questionnaire on Anxiety and Depression Scale was used. Content validity of the questionnaire was established by two experts in Measurement and Evaluation. Cronbach alpha reliability method was used to establish the reliability of the questionnaire. Pearson Product Moment Correlation was used to answer research questions and their corresponding hypotheses at 0.05 alpha level of significance using SPSS version 23. Overall, according to the result, air pollution was found to be positively related to indoor and outdoor crime (domestic violence and robbery). However, air pollution was also found to have a positive association with anxiety and depression. The Ministry of Environment should put in measures to control air pollution. Indoor and outdoor recreation should be promoted to avoid anxiety and depression.